Intra-organizational antecedents of talent management in the context of positive organizational scholarship: a study of companies operating in Poland - Chodorek, Monika; Haffer, Rafał; Lis, Andrzej (Wydawnictwo Uniwersytetu Ekonomicznego we Wrocławiu, 2020)
Purpose: The aim of the study is to empirically validate the influence of talent management antecedents identified in the literature. The concept of talent management is discussed in the context of Positive Organizational Scholarship. This idea helped to prepare a more accurate enumeration of the antecedents of talent management presented in the literature. The analysis of the literature was the basis for developing a set of propositions which constitute the model to be tested empirically. Methodology: The analyses presented in this paper were supported by the data collected in the questionnaire survey conducted among companies operating in Poland in 2012. The examined sample consisted of 73 organizations. Pearson correlation and partial least squares (PLS) path modelling were applied to analyze the causal relations between the variables. Findings: The analysis positively validated the cause-effect relationships between talent management and the following antecedents: talent management infrastructure and organizational culture, organization strategy, and internal communication. Research limitations: The study was limited to companies operating in Poland which established a specific cultural context. The relatively small research sample was another constraint. Therefore, the findings cannot be automatically extended to other organizations. Moreover, in order to reduce the observed ambiguity between causes and effects, quantitative studies should be supported by qualitative surveys based on the case study methodology. Originality/value: The outcomes of the study contribute to the field through the empirical testing of the theoretical assumptions concerning the antecedents of talent management
Argumenta Oeconomica, 2020, Nr 2 (45), s. 231-258
Keywords: talent management; positive organizational scholarship; talent management antecedents